The Determination of Service Quality: Study Literature Review - Sitanggang, Rohana; Dimas Rizky Kusmayadi; Imam Sonny; Tenaka Budiman; Son Wibisono (Dinasti Publisher, 2024)
The Influence of Service Quality, Perception of Tariffs and Facilities on Customer Satisfaction is a scientific article on literature studies within the scope of the field of science. The aim of this article is to build a hypothesis of influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. Research methods using library research come from e-books and open access e-journals. Qualitative descriptive analysis. The results of this article: 1) Service Quality influences Customer Satisfaction; 2) Tariff perceptions influence customer satisfaction; and 3) Facilities influence Customer Satisfaction.